Diversity in anopheline larval habitats and adult composition during the dry and wet seasons in Ouagadougou (Burkina Faso) - Meyer Pierre-Erwann; Ouari Ali; Cussac Maud; Fournet Florence; Toé Hyacinthe K; Gouagna Louis-Clément; Dabiré Roch K (Malaria Journal, 2010)
Abstract Background Several cases of malaria are frequently recorded during the dry period in Ouagadougou town (Burkina Faso). This has led to the design of a series of studies focusing on both parasitological and entomological investigations intended to provide relevant health data on the risk of local malaria transmission according to the way of urbanisation. Methods A cross-sectional entomological survey was carried out in various districts of Ouagadougou in April and October 2006. Adult malaria vectors were collected using CDC traps and indoor insecticide spraying performed in four houses during four consecutive days/nights. Intensive larval sampling was also done in available water ponds throughout the study sites. Results In April, the anopheline breeding sites consisted only of semi-permanent or permanent swamps located mainly in the two peripheral districts. Despite the presence of anopheline larvae in these breeding sites, less than five Anopheles gambiae s.l. adults were caught by CDC traps and indoor insecticide spraying. In October, additionally to the permanent breeding sites reported in April, some rainfall swamps were also found positive to anophelines. The number of adults' mosquitoes was higher than that collected in April (2 vs 159 in October). Out of 115 larvae of An. gambiae s.l. analysed by PCR in April, 59.1% (68/115) were identified as Anopheles arabiensis, 39.1% (45/115) as An. gambiae M while the S form represented less than 2%. Overall 120 larvae and 86 females were identified by PCR in October as An. gambiae M form (51%) and An. arabiensis (42.2%). The S form represented only 6.8%. The global sporozoite rate recorded was high (6.8%) and did not differ between the districts except in the central district where no positive mosquito was detected. Conclusion Although only few adults' mosquitoes were actively caught during the driest month, malaria vectors persisted all year long that increases the risk of urban malaria transmission. The distribution of breeding sites and especially the occurrence of malaria vectors were more abundant in the periphery, which is more like that of a rural settlement. The evolution of malaria prevalence and the factors sustaining the risk of transmission in Ouagadougou as well in many African cities during the dry season are discussed.